2021
DOI: 10.51731/cjht.2021.78
|View full text |Cite
|
Sign up to set email alerts
|

Models of Care for Chronic Pain

Abstract: For chronic pain, 1 hub-and-spoke model and 4 stepped care models for the delivery of care in Canada and internationally were identified and described. No information was found on the use of the Oncology Care Model for chronic pain. For other medical conditions, 9 stepped care models, 5 hub-and-spoke models, and the Oncology Care Model for the delivery of care in Canada and internationally were identified and described. Patient-related outcomes used to evaluate the effectiveness of models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…1,3 Unfortunately, waitlists to access ICPCs are exceptionally long, and in many areas these clinics do not exist. 2 A recent study found that 9 of 10 Canadian provinces have at least 1 ICPC, but most had only 1 clinic per 300,000 people, the majority of whom were located in large urban centres. 2 There are many documented barriers to increasing access to ICPCs, the greatest and most obvious being the significant expense required to operate these clinics.…”
Section: Original Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…1,3 Unfortunately, waitlists to access ICPCs are exceptionally long, and in many areas these clinics do not exist. 2 A recent study found that 9 of 10 Canadian provinces have at least 1 ICPC, but most had only 1 clinic per 300,000 people, the majority of whom were located in large urban centres. 2 There are many documented barriers to increasing access to ICPCs, the greatest and most obvious being the significant expense required to operate these clinics.…”
Section: Original Researchmentioning
confidence: 99%
“…2 A recent study found that 9 of 10 Canadian provinces have at least 1 ICPC, but most had only 1 clinic per 300,000 people, the majority of whom were located in large urban centres. 2 There are many documented barriers to increasing access to ICPCs, the greatest and most obvious being the significant expense required to operate these clinics. 1,3 Additionally, there is a well-documented lack of medical professionals, particularly physicians, who have the specialized training, expertise and willingness to practice in chronic pain.…”
Section: Original Researchmentioning
confidence: 99%
See 3 more Smart Citations